2014
DOI: 10.1007/s11746-014-2546-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of Conjugated Linoleic Acid Rich Soy Oil Obtained by Heterogeneous Catalysis

Abstract: A CLA rich-soy oil (CLARSO) has been produced by heterogenous catalysis. This oil may provide significant health benefits. The objectives of this study were: to determine the oxidative stability of the CLARSO and CLARSO after adsorption treatment [1], relative to conventional soy oil, in terms of primary and secondary oxidation products and to determine CLA and other unsaturated fatty acids oxidation kinetics in the CLARSO [2]. Primary and secondary oxidation products were measured in CLARSO and soy oil sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is reported in the literature that CLAs are more prone to lipid oxidation and analysis on GC-Head space showed that after 3 days of storage of 10% and 20% soybean oil derived CLAs at 65°C decreased by 9.5% and 11.5%, respectively. Supplement having higher extent of CLAs was found to be more susceptible to auto-oxidation (Yettella et al, 2012).…”
Section: Oxidative Stabilitymentioning
confidence: 94%
“…It is reported in the literature that CLAs are more prone to lipid oxidation and analysis on GC-Head space showed that after 3 days of storage of 10% and 20% soybean oil derived CLAs at 65°C decreased by 9.5% and 11.5%, respectively. Supplement having higher extent of CLAs was found to be more susceptible to auto-oxidation (Yettella et al, 2012).…”
Section: Oxidative Stabilitymentioning
confidence: 94%
“…Vegetable oils (as well as fruit oils) and plant extracts are major sources of green cosmeceuticals, which comprise an established area of products for those who wish to age naturally and healthily . The pharmacological effects of bioactive oils can be enhanced through the rational modification of the oils to bioproducts with beneficial functional groups . These intentional and unintentional transformations of vegetable oils provide value added bioproducts and govern product quality .…”
Section: Introductionmentioning
confidence: 99%